RESULTS OF CLINICAL TRIALS IN DENTAL REHABILITATION IN PATIENTS WITH DIABETES 2 TYPE - Kerimov, R.A. (World of Medicine and Biology, 2013)
In a review of 147 medical records of patients with diabetes. Duration of physical illness ranged from 3 years to 26 years. Compensated for diabetes was observed in 24 patients, subcompensated - 4 decompensated - 22. By the time of the initial dental examination, all patients were in stable glycemic control under the supervision of an endocrinologist. Based on an analysis of medical records revealed that the total number of 434 patients had non-removable , and 23 removable design. Of the total number of fixed restorations were made sick - 84 Stamped solder bridges of stainless steel, 324 - metal-ceramic bridges and 26 bridges with plastic. Among removable structures predominated full removable plate dentures made of plastic - 15 units. Partial dentures are made 7 and clasp prosthesis met only in one case, and there was a fixation Preformed clasps. Examination of the oral cavity 147 people found that a prosthesis is not needed, only 7 people. In 140 patients who had different designs of prostheses, including non-removable at 129, removable at 18 people. Among the fixed prosthesis often used metal-ceramic construction of KHS and forged brazed crown of gold, and of dentures - partial plate 7 people, fully removable prosthesis in 11 patients. Needed in the prosthesis 47 human and 34 persons of them replacing existing prostheses because of breakage , any defect or loss of the abutments. The examination revealed that the number of prosthesis need to be manufactured non-removable structure 13, 24 is partially removable, including partial dentures 8 patients.
Keywords: diabetes; prosthesis; orthopedic status; orthopedic care